2021
DOI: 10.3389/fevo.2021.767280
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Physiological Responses to Acute Dehydration in the Rufous-Collared Sparrow: Metabolic, Enzymatic, and Oxidative Traits

Abstract: Predictions indicate that birds worldwide will be affected by global warming and extreme climatic events which is especially relevant for passerines because the diurnal habits, small body size, and high mass-adjusted metabolic rates of this group make it particularly susceptible to increases in temperature and aridity. Some bird species respond to conditions that stress osmoregulation by increasing their rates of energy expenditure, nevertheless, the effect of dehydration on metabolic rates in birds has produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 69 publications
(92 reference statements)
0
5
0
Order By: Relevance
“…Finally, although there is a considerable debate regarding the effects of environmental temperature on oxidative stress in endothermic animals, recent studies revealed that dehydration and temperature may influence oxidative status, yielding an elevated antioxidant response, and/or oxidative damage (Jacobs et al, 2020;Navarrete et al, 2021;Sabat et al, 2019). Thus, we propose that the links between exploratory behavior and oxidative stress might arise…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Finally, although there is a considerable debate regarding the effects of environmental temperature on oxidative stress in endothermic animals, recent studies revealed that dehydration and temperature may influence oxidative status, yielding an elevated antioxidant response, and/or oxidative damage (Jacobs et al, 2020;Navarrete et al, 2021;Sabat et al, 2019). Thus, we propose that the links between exploratory behavior and oxidative stress might arise…”
Section: Discussionmentioning
confidence: 85%
“…Finally, although there is a considerable debate regarding the effects of environmental temperature on oxidative stress in endothermic animals, recent studies revealed that dehydration and temperature may influence oxidative status, yielding an elevated antioxidant response, and/or oxidative damage (Jacobs et al, 2020 ; Navarrete et al, 2021 ; Sabat et al, 2019 ). Thus, we propose that the links between exploratory behavior and oxidative stress might arise in populations exposed to extreme environmental temperatures and/or dehydration, because under these conditions the capacity to counter the oxidative damage resulting from high‐activity levels might be affected by energetic constraints.…”
Section: Discussionmentioning
confidence: 99%
“…While there are several potential mechanisms underlying how climate-/LUCC-change interactions affect ecological communities, the examples in which the dominance of climate corresponded with biodiversity declines suggest the potential for physiological stress (Brown et al ., 2004, Navarrete et al ., 2021, Speakman & Król, 2010) and reduced resource availability (Socolar et al ., 2017) induced by temperature and precipitation changes. This could in turn lead to changes in habitat suitability and the necessity to emigrate to more favorable areas (Heinrichs et al ., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Such increases in metabolic rate could be a mechanism for water production, reducing the need for water conservation and the reliance on (pre-formed) drinking/ food water (see Peña-Villalobos et al, 2013;Sabat et al, 2017). This hypothesis is supported by observations in captive rufous-collared sparrows (Zonotrichia capensis), in which mass loss and an increase in the mass-specific metabolic rates were associated with a higher contribution of metabolic water to the body water pool (Navarrete et al, 2021). No studies have examined this hypothesis in wild birds, and only a handful have quantified the contribution of metabolic water to the water budgets of free-ranging individuals (MacMillen, 1990;Williams and Tieleman, 2001;Giulivi and Ramsey, 2015).…”
Section: Introductionmentioning
confidence: 86%
“…The influence of reproduction on resting rates of energy expenditure (including BMR) in free-ranging birds, however, is controversial (Nilsson, 2002;Chastel et al, 2003;Welcker et al, 2015). While seasonal increases in BMR can be explained by reproductive demands, such changes in metabolic activity may also be an adaptive response to increase metabolic water production (MacMillen, 1990;Navarrete et al, 2021). This hypothesis is consistent with results of both field-and lab-based studies that report increases in mass-specific BMR in freeranging desert birds during the summer (Smit and McKechnie, 2010;McKechnie et al, 2015) and in captive sparrows (Z. capensis) who responded to water restriction by losing mass and increasing their massspecific BMR.…”
Section: Physiological Parameters Linked To Energy and Water Budgetmentioning
confidence: 99%